Recombinant irisin prevents cell death and mineralization defects induced by random positioning machine exposure in primary cultures of human osteoblasts: A promising strategy for the osteoporosis treatment - Cariati, Ida; Bonanni, Roberto; Rinaldi, Anna Maria; Marini, Mario; Iundusi, Riccardo; Gasbarra, Elena; Tancredi, Virginia; Tarantino, Umberto (Frontiers in Physiology, 2023)
Spaceflight exposure, like prolonged skeletal unloading, is known to result in significant bone loss, but the molecular mechanisms responsible are still partly unknown. This impairment, characterizing both conditions, suggests the possibility of identifying common signalling pathways and developing innovative treatment strategies to counteract the bone loss typical of astronauts and osteoporotic patients. In this context, primary cell cultures of human osteoblasts derived from healthy subjects and osteoporotic patients were exposed to random positioning machine (RPM) to reproduce the absence of gravity and to exacerbate the pathological condition, respectively. The duration of exposure to RPM was 3 or 6 days, with the aim of determining whether a single administration of recombinant irisin (r-irisin) could prevent cell death and mineralizing capacity loss. In detail, cellular responses were assessed both in terms of death/survival, by MTS assay, analysis of oxidative stress and caspase activity, as well as the ex-pression of survival and cell death proteins, and in terms of mineralizing capacity, by investigating the pentraxin 3 (PTX3) expression. Our results suggest that the effects of a single dose of r-irisin are maintained for a limited time, as demonstrated by complete protection after 3 days of RPM exposure and only partial protection when RPM exposure was for a longer time. Therefore, the use of r-irisin could be a valid strategy to counteract the bone mass loss induced by weightlessness and osteoporosis. Further studies are needed to determine an optimal treatment strategy based on the use of r-irisin that is fully protective even over very long periods of exposure and/or to identify further approaches to be used in a complementary manner.